Factors Associated with Utilisation of Couple HIV Counselling and Testing Among HIV‑Positive Adults in Kyoga Fishing Community Uganda, May 2017: Cross Sectional Study - Nakiire, Lydia; Kabwama, Steven; Majwala, Robert; Kusiima Bbale, Joy; Makumbi, Issa; Kalyango, Joan; Kihembo, Christine; Masiira, Ben; Bulage, Lilian; Kadobera, Daniel; Riolexus Ario, Alex; Nsubuga, Peter; et al. (AIDS and behavior, 2020)
Couple HIV counseling and testing (CHCT) is key in preventing heterosexual HIV transmission and achievement of 90-90- 90 UNAIDS treatment targets by 2020. We conducted secondary data analysis to assess utilization of CHCT and associated factors using logistic regression. 58/134 participants (49%) had ever utilized CHCT. Disclosure of individual HIV results to a partner [aOR = 16; 95% CI: (3.6–67)], residence for > 1 < 5 years [aOR = 0.04; 95% CI (0.005–0.33)], and none mobility [aOR = 3.6; 95% CI (1.1–12)] were significantly associated with CHCT. Age modified relationship between CHCT and disclosure (Likelihood-ratio test LR chi2 = 4.2 (p value = 0.041). Disclosure of individual HIV results with a partner and residence for more than 1 year improved utilization of CHCT; mobility reduced the odds of CHCT. Interventions should target prior discussion of individual HIV results among couples and mobile populations to increase CHCT.
Keywords: Couple; HIV counseling & testing; Fishing community